Phytotoxicity of wear debris from traditional and innovative brake pads. (February 2019) - Maiorana, Simone; Teoldi, Federico; Silvani, Sara; Mancini, Alessandro; Sanguineti, Alessandro; Mariani, Federico; Cella, Claudia; Lopez, Aitziber; Potenza, Marco Alberto Carlo; Lodi, Marco; Dupin, Damien; Sanvito, Tiziano; et al.
Abstract: Traffic-related emissions include gas and particles that can alter air quality and affect human and environmental health. Limited studies have demonstrated that particulate debris thrown off from brakes are toxic to higher plants. The acute phytotoxicity of brake pad wear debris (BPWD) investigated using cress seeds grown in soil contaminated with increasing concentrations of debris. Two types of pads were used: a commercially available phenol based pad and an innovative cement-based pad developed within of the LIFE+ COBRA project. The results suggested that even through the BPWD generated by the two pads were similar in and morphology, debris from traditional pads were more phytotoxic than that from cementitious pads, causing significant alterations in terms of root elongation and loss of plasma membrane integrity. Graphical abstract: Unlabelled Image Highlights: Phytotoxicity of brake pads-derived debris was studied integrating different approaches. Debris generated by two different pads were analyzed. FE-SEM and SPES analyses were used to characterize the debris. Effects on seed germination, root elongation and plasma membrane integrity were evaluated. Debris from traditional pads are generally more toxic than those from the innovative pads.